2005
DOI: 10.1122/1.2048741
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative prediction of transient and steady-state elongational viscosity of nearly monodisperse polystyrene melts

Abstract:  Users may download and print one copy of any publication from the public portal for the purpose of private study or research.  You may not further distribute the material or use it for any profit-making activity or commercial gain  You may freely distribute the URL identifying the publication in the public portal If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
119
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 115 publications
(128 citation statements)
references
References 22 publications
7
119
2
Order By: Relevance
“…Such behaviour was only predicted by previous models using unrealistically low values of the chain finite extensibility parameter [1,15]. A further model of interchain tube pressure effect was then proposed by Marrucci and Ianniruberto [17] to explain Bach et al [16] results, followed by macroscopic constitutive equations from Wagner et al [18] and Dhole et al [1] that were able to quantitatively predict them. The present study aimed at checking the validity of the model of Dhole et al in both rheometrical and complex flows, for a polydisperse polystyrene melt.…”
Section: Introductionmentioning
confidence: 94%
“…Such behaviour was only predicted by previous models using unrealistically low values of the chain finite extensibility parameter [1,15]. A further model of interchain tube pressure effect was then proposed by Marrucci and Ianniruberto [17] to explain Bach et al [16] results, followed by macroscopic constitutive equations from Wagner et al [18] and Dhole et al [1] that were able to quantitatively predict them. The present study aimed at checking the validity of the model of Dhole et al in both rheometrical and complex flows, for a polydisperse polystyrene melt.…”
Section: Introductionmentioning
confidence: 94%
“…It initially consists of a 60-nm-thick polymeric film of a 390 kg/mole polystyrene, where we use a value of τ w /3 = 0.035τ max . 13,23 All material parameters can be found in Wagner et al 13 and Bach et al 23 After a time delay, the initial disturbance gradually evolves and the local thickness goes toward zero, which by definition is the critical point in time where the hole develops. Only one hole develops from a disturbance, and the surface remains flat between the holes.…”
Section: Computational Detailsmentioning
confidence: 99%
“…de Gennes. 12 While the original Doi and Edwards model 11 has many limitations, Wagner et al 13 added a stretch equation based on the "interchain pressure" concept. 14 This approach is currently the most accurate model to predict the flow behavior of monodisperse polymer melts.…”
Section: Computational Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…More recent developments of the MSF model for linear and branched monodisperse polystyrene melts [6][7][8] have shown that for modeling of monodisperse melts an application of only one nonlinear parameter is sufficient. This parameter, the so-called tube diameter relaxation time a W , represents the relaxation of the topological constraint caused by many surrounding chains.…”
Section: Introductionmentioning
confidence: 99%